Diet and physical activity are associated with suboptimal weight loss and weight regain 10–15 years after Roux-en-Y gastric bypass: A cross-sectional study. Issue 2 (March 2022) - Nymo, Siren; Lundanes, Julianne; Aukan, Marthe; Sandvik, Jorunn; Johnsen, Gjermund; Græslie, Hallvard; Larsson, Ingrid; Martins, Catia
Abstract: Introduction: Suboptimal weight loss (SWL) after bariatric surgery affects approximately 30% of the patients in the long-term. Diet and physical activity (PA) are likely to modulate long term weight loss outcomes after Roux-en-Y gastric bypass (RYGB). Objectives: To compare food habits and PA levels between those experiencing SWL and optimal weight loss (OWL), and between those experiencing weight regain (WR) and no weight regain (NWR), 10–15 years after RYGB, in addition to a pre-operative control group. Methods: Participants were recruited from the Bariatric Surgery Observation Study (BAROBS), ≥ 10 y after RYGB. Food intake was assessed by a Food Frequency Questionnaire (FFQ) and PA levels with Sensewear armbands. Results: 75 participants (79% females) were recruited. Excess weight loss (EWL) was 17 ± 19% and 87 ± 22% in the SWL and OWL groups, respectively and WR was 31 ± 15% and 1 ± 11% in the WR and NWR groups, respectively (P < 0.001 for both). The OWL group reported a lower energy intake (P = 0.012) than the control group. The control group reported a higher intake of milk, cream and cheese than both SWL group (P = 0.008) and OWL group (P < 0.001). The SWL group reported a higher intake of processed meat products than the OWL group, while the OWL group reported a lower intake of sauces than both the SWL and the control groups (P < 0.001 and P = 0.005, respectively). The OWL group reported a lower intake of cakes, sugar and sweets than both SWL group (P = 0.035) and control group (P = 0.021). The WR group reported a lower PA duration (P = 0.046) compared with the NWR group. EWL was positively, and WR negatively, correlated with average PA duration. Conclusion: A high intake of energy-dense foods and low PA is associated with poor weight loss outcomes, namely SWL and WR, 10–15 years after RYGB. Highlights: The dietary habits of participants with suboptimal weight loss after RYGB are similar to individuals with severe obesity. A higher intake of sugar-rich, energy dense foods is associated with poorer long-term weight loss outcomes after RYGB. A higher intake of protein and processed meat products is associated with poorer long-term weight loss outcomes after RYGB. Reduced physical activity levels are associated with poorer long-term weight loss outcome after RYGB.